The governance of daily life in Africa : ethnographic explorations of public and collective services - Blundo, Giorgio; Le Meur, Pierre-Yves, 1962- (African social studies series ;, 2009)
Explores the notion of governance in a non-normative way. This work describes and analyses the institutional and political processes through which social actors and groups - be they state, private or 'third-sector' - contribute to the provision of public and collective goods or services.